Studi Analisis Akurasi Perhitungan Awal Waktu Shalat Menggunakan Universal Astrolabe - Hadi, Imron (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2022)
Universal Astrolabe is a type of Astrolabe that can be used in any region or latitude. This paper examines the accuracy of the Universal Astrolabe in determining the start of the five daily prayer times (Fajr, Zuhur, Asr, Maghrib and Isha). The purpose of this study was to determine the accuracy of the calculation method for determining the beginning of prayer times using the Universal Astrolabe. Astrolabe is one of the classical astronomical instruments that describes the celestial sphere in two dimensions and was originally used to determine the position of the Sun. Astrolabe comes from the Greek language which consists of the word "aster" which means star, and the word "labio" which means take, understand, and catch. In simple terms, Astrolabe can be interpreted as a tool to study the Stars. This instrument is a type of calculating tool. The function of the Astrolabe is very complex, namely to determine the position of the Sun or other stars, to determine the zodiac and its circulation scale, to determine the height of an object and determine solar time. The results showed that the method of calculating the initial prayer time applied in the Universal Astrolabe was the method of reading directly on the plate. The initial calculation of prayer times using the Universal Astrolabe results in a calculation difference between 0-3 minutes and the prayer time schedule set by the Ministry of Religion of the Republic of Indonesia, so it is considered quite accurate. This difference can be influenced by the diameter of the Universal Astrolabe and the accuracy of the reader when reading the curves and numbers listed on the Universal Astrolabe.Keywords: Prayer Times, Accuracy, Universal Astrolabe.